1974
DOI: 10.1136/adc.49.10.796
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal secretion of gastrin and glucagon

Abstract: (1974). Archives of Disease in Childhood, 49, 796. Neonatal secretion of gastrin and glucagon. Plasma gastrin and glucagon levels were estimated in mothers after labour, and in their babies at birth and on the fourth day of life. The newly born baby appears to secrete gastrin independently and the plasma levels are higher on the fourth day of life. The cord gastrin level is lower when labour is induced or augmented by the intravenous infusion of oxytocin. Our results do not exlude the possibility that gastrin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

1975
1975
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(50 citation statements)
references
References 18 publications
3
45
0
2
Order By: Relevance
“…Our results do show that both arterial and venous gastrin levels are higher after spontaneous labour, which confirms our previous observation on the influence of oxytocin infusion on cord gastrin levels (Rogers et al, 1974).…”
Section: Discussionsupporting
confidence: 93%
“…Our results do show that both arterial and venous gastrin levels are higher after spontaneous labour, which confirms our previous observation on the influence of oxytocin infusion on cord gastrin levels (Rogers et al, 1974).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed one study showed that mean basal acid output was at its lowest on the tenth day of life, which is about the time when PYY levels are highest (22). Hypergastrinemia has been reported at this stage and is probably a physiologically important event because gastrin is trophic to the antral mucosa (22)(23)(24). High PYY levels may suppress the acid hypersecretion that would otherwise occur.…”
Section: Methodsmentioning
confidence: 99%
“…Rogers et al (6) reported that oxytocin use during labor caused a lower cord gastrin level than when infants were spontaneously delivered. We could not confirm this observation.…”
Section: Euler and Walshmentioning
confidence: 99%